2019
DOI: 10.29252/jcc.1.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cu-Substitution on the Microstructure and Magnetic Properties of Fe-15%Ni alloy Prepared by Mechanical Alloying

Abstract: In this study, nanostructured (Fe 85 Ni 15) 100-x Cu x (x = 0, 0.5, 1.5, 3 and 5) powders were synthesized via mechanical alloying process. The obtained phases, microstructure, and magnetic properties of these alloys were studied by X-ray diffraction analysis (XRD), scanning electron microscopy (SEM), and vibration sample magnetometer (VSM). XRD results indicated that after a suitable time of milling, Ni and Cu were homogeneously distributed in the Fe matrix, and (bcc) α-(Fe(Ni-Cu)) solid solution was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…Moreover, the sodium hydroxide and temperature role in the ZnO preparation nanoparticles were studied by Mayekar et al [44]. Their study showed that the size of the particle was increased by raising the temperature and also with a rising concentration of sodium hydroxide [45,46]. Chemical synthesis is the most principle procedure and contains vast amounts of precursors and variable factors such as time, the concentration of reactants, temperature, etc.…”
Section: Formation Of Zno Nanoparticles Via Sol-gel Methodsmentioning
confidence: 99%
“…Moreover, the sodium hydroxide and temperature role in the ZnO preparation nanoparticles were studied by Mayekar et al [44]. Their study showed that the size of the particle was increased by raising the temperature and also with a rising concentration of sodium hydroxide [45,46]. Chemical synthesis is the most principle procedure and contains vast amounts of precursors and variable factors such as time, the concentration of reactants, temperature, etc.…”
Section: Formation Of Zno Nanoparticles Via Sol-gel Methodsmentioning
confidence: 99%
“…Cu is the best selection for integrates circuits, especially microprocessors due to its improved electromigration performance as well as low resistivity [158][159][160][161][162]. Under neutral pH conditions, protective oxide or hydroxide layers form on the surface of Cu substrates [163][164][165][166][167]. In chloride-containing environments, the copper corrosion process and the protective layer formation are more complex [168,169].…”
Section: Ccps Coated On Copper and Its Alloysmentioning
confidence: 99%
“…By alloying magnesium with zirconium [33], zinc [34], thorium [35], manganese [36], aluminum [37], or rare earth metals [38], the ratio of strength to weight increases, making these materials suitable choices where lightweight and the reduction of inertial forces are required. Due to this characteristic, denser cast iron, steel, copper-based alloys, and even Al-based alloys are replaced with Mg-based alloys [39,40]. Mg is very appealing to the electronic and audio industry owing to its significant electromagnetic interference shielding [41,42].…”
Section: Mg and Its Alloysmentioning
confidence: 99%